SEGMENTING, TARGETING AND POSITIONING ANALYSIS OF MSME FURNITURE BASUKI LACASA MALANG - Novita Rifaul Kirom; Sudarmiatin Sudarmiatin (International Journal Labs, 2022)
At the end of 2019 Indonesia began to enter the Covid-19 pandemic which caused a decline in the turnover of several MSMEs. So it is necessary to carry out market research. In determining the need for furniture in the market, every MSME in the furniture sector must carry out a market strategy, one of the market strategies is segmenting, targeting and positioning (STP). In this strategy, it is possible to divide heterogeneous prospective customers into homogeneous prospective customers so that market conditions can be easily entered by MSMEs, especially in the furniture sector. The aims of this study are: 1) to determine the suitability of market segmentation carried out by MSME furniture, Basuki Lacasa; 2) determine the suitability of the target market carried out by MSME Basuki Lacasa; 3) to find out the results of the position of MSME Basuki Lacasa in the market. The method in this research is qualitative with 1 key informant and 3 co-informants. The final result obtained in this research is the application of segmenting, targeting and positioning that has been carried out in accordance with market conditions. STP (Segmenting, Targeting, Positioning) carried out by UMKM Furniture Basuki Lasaca are as follows: (a) the targeted market segments are the upper social class, lower social class and middle social class, (b) the selected target market is in the form of segment concentration or single market, (c) Basuki Lasaca furniture is positioned as furniture with high quality.